Threonine Phosphorylation Fine-Tunes the Regulatory Activity of Histone-Like Nucleoid Structuring Protein in Salmonella Transcription - Hu, Lizhi; Kong, Wei; Yang, Dezhi; Han, Qiangqiang; Guo, Lin; Shi, Yixin (Frontiers in Microbiology, 2019)
Histone-like nucleoid structuring protein H-NS in enterobacteria plays an important role in facilitating chromosome organization and functions as a crucial transcriptional regulator for global gene regulation. Here, we presented an observation that H-NS of Salmonella enterica serovar Typhimurium could undergo protein phosphorylation at threonine 13 residue (T13). Analysis of the H-NS wild-type protein and its T13E phosphomimetic substitute suggested that T13 phosphorylation lead to alterations of H-NS structure, thus reducing its dimerization to weaken its DNA binding affinity. Proteomic analysis revealed that H-NS phosphorylation exerts regulatory effects on a wide range of genetic loci including the PhoP/PhoQ-regulated genes. In this study, we investigated an effect of T13 phosphorylation of H-NS that rendered transcription upregulation of the PhoP/PhoQ-activated genes. A lower promoter binding of the T13 phosphorylated H-NS protein was correlated with a stronger interaction of the PhoP protein, i.e., a transcription activator and also a competitor of H-NS, to the PhoP/PhoQ-dependent promoters. Unlike depletion of H-NS which dramatically activated the PhoP/PhoQ-dependent transcription even in a PhoP/PhoQ-repressing condition, mimicking of H-NS phosphorylation caused a moderate upregulation. Wild-type H-NS protein produced heterogeneously could rescue the phenotype of T13E mutant and fully restored the PhoP/PhoQ-dependent transcription enhanced by T13 phosphorylation of H-NS to wild-type levels. Therefore, our findings uncover a strategy in S. typhimurium to fine-tune the regulatory activity of H-NS through specific protein phosphorylation and highlight a regulatory mechanism for the PhoP/PhoQ-dependent transcription via this posttranslational modification.